Development of the Salted Egg Industry in Limbangan Wetan Village, Brebes District and its Influence on Community Socio-Economics 1980-2005 as a Learning Resource - Amrillah, Diyan Hayyu (Universitas Negeri Semarang, 2017)
This study aims to determine 1) the development of the salted egg industry in the village of Bradford District Limbangan Wetan in 1980-2005, and 2) the process of making salted eggs and innovations developed by salted egg industry employers in the Village District Limbangan Wetan Bradford, and 3) influence the development of salted egg industry in the village of Bradford District Limbangan Wetan. The method used in this paper is historical research because it is related to the fact that it occurred during the study. Based on the following results, The effect of the salted egg industry on economic and social impact is devastating for the people of Bradford district. Salted egg industry development has brought many changes in people's lives. Bradford District is providing new jobs for the people who can reduce unemployment and increase incomes, which would undoubtedly improve the community's welfare and reduce urbanization, giving birth to new entrepreneurs in terms of education to improve workers' education.